Propuesta de turismo sostenible para la zona de uso turístico del Parque Nacional Podocarpus en el Centro Administrativo de Bombuscaro, del cantón Zamora - Zúñiga Sarango, Vanessa del Cisne (2023)
The present research work has as general objecve Propose a sustainable strategic plan of tourist pracces for the tourist use zone of the Podocarpus Naonal Park (PNP) in the Administrave Center of Bombuscaro, of the Zamora canton in order to achieve all the compliance of that invesgaon. raised 3 specific objecves the first where he carried out a survey of the park's tourist resources and informaon inventory, for the development of this a documentaon validaon matrix was used where documentary informaon of the Podocarpus Naonal Park was collected, based on the Global criteria Sustainable Tourism Council (GSTC) which helped to know which is the documentaon with which the Park complies. The second objecve, which was to diagnose the sustainable tourism pracces that are developed in the PNP, this was done through a weighng matrix and as well as a SWOT and CROSS SWOT matrix, leng us know which of the 3 performance indicators that They are Sustainable management, Socio-Economic Sustainability, Environmental Sustainability, idenfying which one has more compliance weight, obtaining as a result that in socio-economic sustainability, the requirements of each criterion are more fulfilled, through the CROSSED SWOT matrix, strategies were proposed to each internal and external factor for the help of the realizaon of the acon plan of the next objecve. The last objecve where three acon plans were proposed based on the 3 criteria evaluated, for the development of this objecve the acon plan matrix of the Ministry of the Environment was applied, proposing objecves, strategies and results, this helping to achieve the goals , propose the measures that must be executed to correct the lack of sustainable development within the protected area. Concluding with the invesgaon, it was determined that the park has several shortcomings in the economic, sustainable, and above all, to propose alliances and new projects to obtain beter sustainability and management of the park.